Study of Single Nucleotide Polymorphisms Associated with Breast Cancer Patients among Arab Ancestries. (11th October 2022) - Osman, Yasser; Elsharkawy, Tarek; Hashim, Tariq Mohammad; Alratroot, Jumana Abdulwahab; Aljindan, Fatima; Almulla, Liqa; Alsuwat, Hind Saleh; Al Otaibi, Waad Mohammed; Hegazi, Fatma Mohammed; Ibrahim, Abdallah M.; Borgio, J. Francis; AbdulAzeez, Sayed
Abstract : The aim of this study is to investigate the single nucleotide polymorphisms (SNPs) associated with breast cancer in our population of Arab patients. We investigated 26 breast cancer patients and an equal number of healthy age- and sex-matched control volunteers. We examined the exome wide microarray-based biomarkers and screened 243, 345 SNPs for their possible significant association with our breast cancer patients. Successfully, we identified the most significant (p value ≤ 9.14 × 10 − 09 ) four associated SNPs [ SNRK and SNRK-AS1- rs202018563G; BRCA2- rs2227943C; ZNF484- rs199826847C; and DCPS- rs1695739G] among persons with breast cancer versus the healthy controls even after Bonferroni corrections (p value < 2.05 × 10 − 07 ). Although our patients' numbers were limited, the identified SNPs might shed some light on certain breast cancer-associated functional multigenic variations in Arab patients. We assert on the importance of more extensive large-scale analysis to confirm the candidate biomarkers and possible target genes of breast cancer among Arab ancestries.